2014
DOI: 10.1016/j.molcel.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

NuA4 Initiates Dynamic Histone H4 Acetylation to Promote High-Fidelity Sister Chromatid Recombination at Postreplication Gaps

Abstract: Summary CAG/CTG trinucleotide repeats are unstable, fragile sequences that strongly position nucleosomes, but little is known about chromatin modifications required to prevent genomic instability at these or other structure-forming sequences. We discovered that regulated histone H4 acetylation is required to maintain CAG repeat stability and promote gap-induced sister chromatid recombination. CAG expansions in the absence of H4 HATs NuA4 and Hat1 and HDACs Sir2, Hos2, Hst1 depended on Rad52, Rad57, and Rad5, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 59 publications
1
72
0
Order By: Relevance
“…The role of H4 acetylation in the DNA damage response is to loosen nucleosome interactions and to serve as a substrate for chromatin remodelers such as SWR1-C and RSC2. Similar to H2A.Z, histone H4 acetylation is important for error-prone/TLS; however, in contrast to H2A.Z, but consistent with House et al (2014), we found that H4 acetylation is also important in error-free bypass after exposure to MMS. Interestingly, cells harboring hhf2 K/R led to a greater loss of viability when combined with rev3D ( Figure 4A) compared to the NuA4/ rev3D double mutants, perhaps indicating NuA4-independent modifications to histone H4 in error-free bypass.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The role of H4 acetylation in the DNA damage response is to loosen nucleosome interactions and to serve as a substrate for chromatin remodelers such as SWR1-C and RSC2. Similar to H2A.Z, histone H4 acetylation is important for error-prone/TLS; however, in contrast to H2A.Z, but consistent with House et al (2014), we found that H4 acetylation is also important in error-free bypass after exposure to MMS. Interestingly, cells harboring hhf2 K/R led to a greater loss of viability when combined with rev3D ( Figure 4A) compared to the NuA4/ rev3D double mutants, perhaps indicating NuA4-independent modifications to histone H4 in error-free bypass.…”
Section: Discussionsupporting
confidence: 70%
“…Chromatin reassembly after fork passage and how the chromatin environment contributes to DDT function is only starting to be considered (Falbo et al 2009;Ball et al 2014;Gonzalez-Huici et al 2014;House et al 2014;Kim et al 2014). Our data indicate that the histone acetyltransferase, NuA4, has a role in DDT with a measureable role in error-prone/TLS bypass.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Besides chromatin relaxation, Tip60-mediated acetylation of phospho-H2Av, 飦2AX homolog in Drosophila melanogaster, induces the exchange of phospho-H2Av with unmodified H2Av (Kusch et al, 2004), while Tip60-dependent H4K16 acetylation diminishes 53BP1 binding to H4K20me2 and promotes HR repair (Tang et al, 2013). Tip60 depletion impairs homologous recombination and rendered cells sensitive to cisplatin (House et al, 2014;Miyamoto et al, 2008;Tang et al, 2013). Furthermore, similar to human CBP/p300 or yeast Rtt109, histone acetyltransferase 1 in yeast and human cells is also required for the incorporation of acetylated H3 at sites of double-strand breaks, and facilitates subsequent recruitment of RAD51 to promote efficient homologous recombination (Qin and Parthun, 2002;Yang et al, 2013).…”
Section: Acetylationmentioning
confidence: 99%
“…NuA4 acetylates lysines on the N-terminal tails of H4, H2A, and H2AZ (Htz1) histones (7,(9)(10)(11)(12), and its histone acetyltransferase (HAT) activity is important for the regulation of gene transcription (13)(14)(15)(16)(17)(18)(19)(20)(21) and also for the cellular response to DNA dam-age, recombination, and DNA double-strand break repair (22)(23)(24)(25)(26)(27). More recently, NuA4 was also shown to regulate life span and autophagy through its ability to acetylate nonhistone proteins (28)(29)(30).…”
mentioning
confidence: 99%